2004
DOI: 10.1103/physrevb.69.041308
|View full text |Cite
|
Sign up to set email alerts
|

Electron paramagnetic resonance study ofZn1xCoxO:A predict

Abstract: The magnetic properties of Co 2ϩ ions in epitaxial ͑Zn,Co͒O layers with 10% Co concentration have been studied by electron paramagnetic resonance spectroscopy. The Co-related EPR spectrum is characterized by a 200-G broad anisotropic single line with g factors close to those of the isolated Co 2ϩ ion. The temperature dependence of the EPR signal follows a Curie-Weiss law with a critical temperature of ϩ12 K. We find no evidence for a high-temperature ferromagnetic state. Magnetocrystalline anisotropy is observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
64
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(71 citation statements)
references
References 16 publications
(11 reference statements)
6
64
0
Order By: Relevance
“…7-9͒ in which Co is substituted for Zn rather than forming clusters. These studies also show that nanocrystalline Zn 1−x Co x O is paramagnetic in this concentration range and at low temperature; 8,9 ferromagnetism was observed only at very low temperature. Another agent must therefore be responsible for promotion of high-T c ferromagnetism in Zn 1−x Co x O.…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…7-9͒ in which Co is substituted for Zn rather than forming clusters. These studies also show that nanocrystalline Zn 1−x Co x O is paramagnetic in this concentration range and at low temperature; 8,9 ferromagnetism was observed only at very low temperature. Another agent must therefore be responsible for promotion of high-T c ferromagnetism in Zn 1−x Co x O.…”
Section: Introductionmentioning
confidence: 54%
“…Recent magnetic resonance, [27][28][29][30][31][32] carrier mobility, 33 positron annihilation spectroscopy, 34 and first-principles calculations [35][36][37] have given a fuller picture of defect-induced electronic states in ZnO. Magnetic resonance techniques 8,9,38 have been applied to Zn 1−x Co x O and Zn 1−x Mn x O films and nanoclusters. As noted above, these studies 8,9,38,39 as well as x-ray magnetic circular dichroism, 12,39 which probe the local crystal structure about the transition-metal ion, have concluded that the transition-metal ions substitute for a Zn ion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] Even in systems that appear to be quite pure, reported magnetic behavior can vary widely, ranging from room-temperature ferromagnetism 6 to no magnetic ordering at all. 7,8 This variance in magnetism is attributed to the multitude of synthetic methods used for the production of DMS materials, which can result in differences in dopant environment, structural disorder, or carrier concentration. Therefore, to extract the most accurate information from any magnetic data on a DMS material, it is vital to perform a rigorous structural characterization.…”
mentioning
confidence: 99%
“…In particular, the theoretical predictions based on the local spin density approximation (LSDA), triggered extensive studies of ZnO :TM alloys with a special focus on ZnO :Co as the most promising candidate for a room-temperature ferromagnetic (FM) semiconductor [5]. Many experiments have been reported on this material fabricated by a variety of methods [6,7,8,9,10,11,12,13,14,15,16,17,18,19] ; however, the magnetic properties of ZnO :Co still remain a controversial issue since the observed magnetic behavior appears to be strongly dependent on the preparation methods and is poorly reproducible.…”
mentioning
confidence: 99%